Effects of a Self-Management Support Program on Knowledge, Anxiety, and Self-Care Behaviors in Women with a Low-Grade Squamous Intraepithelial Cervical Lesion: A Quasi-experimental Study. - Pornsinsiriruck, Sarwitree; Arpanantikul, Manee; Sumdaengrit, Bualuang; Lertkhachonsuk, Arb-aroon; Grube, Wendy D. (Pacific Rim International Journal of Nursing Research)
Low-grade squamous intraepithelial lesions, which represent mild abnormalities in cervical cytology, are being identified with increasing frequency among women. Encouraging effective self-care practices is a key strategy for preventing or slowing the progression of precancerous cervical conditions. This quasi-experimental study was part of a larger study aimed at developing and evaluating the impact of a self-management support program. We employed an integrated framework of self-management theory and feminist theory on women's knowledge, anxiety levels, and self-care behaviors following a diagnosis of low-grade cervical cytological abnormalities. A total of 50 eligible women were purposively selected from a university hospital in Bangkok, Thailand. Participants were allocated sequentially, with the comparison group (n = 25) enrolled prior to the experimental group (n = 25). Women in the experimental group received the self-management support program in addition to standard care, whereas those in the comparison group received standard care alone. Data were collected between May 2020 and June 2021 using the Personal Information Questionnaire, the Knowledge of Abnormal Cervical Cytology Questionnaire, the State-Trait Anxiety Inventory, and the Health-Promoting Lifestyle Profile II. Statistical analyses included descriptive statistics, the chi-square test, independent t-test, Wilcoxon signed-rank test, Mann--Whitney U test, and ANCOVA. The findings demonstrated a significant improvement in self-care behaviors among participants in the experimental group only. Post-intervention comparisons showed that women who received the self-management support program achieved significantly higher levels of knowledge and self-care behaviors than those receiving usual care alone. However, no significant difference in state anxiety was observed between the two groups. Overall, the results suggest that the self-management support program was effective in increasing knowledge and promoting positive health behaviors, although it did not significantly reduce anxiety. This program requires further testing in other groups before application to practice by nurses as an educational and empowerment tool to support women with low-grade squamous intraepithelial lesions in managing their health and reducing the risk of cervical cancer progression through practical guidance and accessible resources.